Somatostatin analog octreotide inhibits the growth of differentiated thyroid cancer cells in vitro, but not in vivo - Hölting, Thomas; Duh, Quan-Yang; Clark, Orlo H.; Herfarth, Christian (The journal of clinical endocrinology & metabolism, 1996)
Somatostatin and its analogs are antiproliferative in a wide range of normal and neoplastic tissues. In this study we investigated the effect of octreotide (SMS 201-995) on the invasion and growth of three follicular thyroid cancer (FTC) cell lines from one patient in vitro and in vivo. FTC133 was established from the primary tumor, FTC236 from a cervical lymph node metastasis, and FTC238 from a lung metastasis. Invasion was the ability of tumor cells to penetrate 8-microns pore polycarbonate membranes coated with Matrigel. Invasion and proliferation were analyzed using the MTT assay. For in vivo experiments, athymic nude mice were sc inoculated with 500,000 calls of FTC133. The animals were treated twice daily with octreotide sc (100-300 micrograms/kg). RIA studies yielded dose-dependent high plasma levels of octreotide (3.43-6.5 ng/mL). Octreotide had a biphasic effect, enhancing growth at low concentrations (1-10 nmol/mL) and inhibiting it at high concentrations (100 nmol to 1 mumol/mL). Octreotide had also a dose-dependent biphasic effect on the invasion of FTC, inhibiting the invasion of all follicular thyroid cancer lines at high concentrations. However, it affected invasion less than growth. Octreotide (10 nmol/mL) stimulated the invasion of FTC133 by 13%, whereas stimulation was lower in both FTC metastases (FTC236, 6%; FTC238, 7%; P < 0.01). At higher concentrations (100 nmol to 1 mumol/mL), octreotide inhibited invasion of FTC133 by 17% (FTC236, 15%; FTC238, 17%; P < 0.01). During a 3-week treatment period, octreotide had no antiproliferative effect on the growth of FTC133 cells in nude mice. In conclusion, octreotide at low concentrations stimulates and at high concentrations inhibits the growth and invasion of follicular thyroid cancer cells in culture. However, it has no effect on the growth of FTC cells in animal experiments. Thus, the value of octreotide as an antitumoral agent in follicular thyroid cancer must be critically questioned.
Gesehen am 20.08.2025